KEBERADAAN KOMITE AUDIT SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN PADA PEMBERIAN OPINI GOING CONCERN - Devi, Clara Azelia; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of firm size on giving opinions going concern and the existence of audit committee in moderating the effect of firm size on giving opinions going concern. The study was conducted at the manufacturing companies listed in Indonesia Stock Exchange year period 2012-2014. Samples were obtained by 69 companies with non-probability sampling methods, particularly purposive sampling. Data analysis technique used is logistic regression analysis approach moderated regression analysis (MRA). The analysis finds that the size of the company's significant negative effect on the administration of going concern opinions and the existence of an audit committee is not able to moderate the influence of the size of the company in the provision of a going concern opinion.
Keywords: Going Concern Opinion, Company Size, Audit Committee, Good Corporate Governance